The fluctuations and anomalies of climatic elements in the undulating region of Iraq - Fadel, Huda Raisan; Al-Nouri, Sulaf Adnan Jaber (Al-Adab Journal, 2021)
The study is about the issue of climate volatility and its effect on the anomalies of some climatic elements in the undulating region of Iraq. Five stations were chosen representing the undulating region (Sinjar, Mosul, Kirkuk, Tuz, Khanaqin). The study also touched on the concept of climate volatility, and the difference ratio equation was used to extract the volatility values of climatic elements, and it was concluded through this that there is a volatility in climatic elements in the study area where the highest volatility of solar radiation was recorded at the Khanaqin station. It reached (4.1 mW / cm2 / day), as for temperature volatility, the Toz station recorded the highest rate of volatility, reaching (4.7) degrees Celsius, as for the fluctuation of rain, the Sinjar station recorded the highest fluctuation, which reached (41.7 mm) due to the influence of the dynamic factors as well as the height factor.